Making the Cuban Science visible vs providing prestige to national journals? - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Scientific Cuban production, in particular the one framed in the bio-medical environment, requires a higher visibility. This is possible by means of locating articles derived from it in the medical journals of more circulation worldwide. At the same time, there is a logical intention of improving and providing prestige to Cuban journals. In this article, it is specifically approached, the dilemma between the convenience of publishing in foreign high impact journals or doing it in national journals. It is highlighted the need of indexing national journals in international database. In this way, Cuban research, which is mostly published in these journals, could have a wider dissemination.